World-class good governance ethics : A key solution to tackle criminal acts in Malaysian public-listed companies - Wan Ahmad Fauzi, Hashim @ Wan Husain; Mohamad Reeduan, Mustapha; Fernando, Yudi; Siti Aisyah, Ahmad Zailani (Emerald Publishing, 2023)
The purpose of this study is to propose a world-class good governance ethics framework that leads to better corporate performance. ethics among managers, executives and members of the board of directors working in public-listed companies brings grave concern because of the increasing number of criminal acts reported by the Security Commission of Malaysia. Design/methodology/approach: This study introduces a world-class good governance ethics framework for curbing criminal acts in public-listed companies in Malaysia. This study used a mixed method to gather data, and the methods used are appropriate for answering the research questions based on the World-Class Good Governance Ethics framework. Findings: The finding of this study reveals high expectations for a corporate organization to improve individual and team performance while undertaking their corporate responsibilities, and a matter of choice, to adopt world-class good governance ethics in their policies and practices. Practical implications: This study could be a reference for corporate management to regulate policies monitoring management's and employees' conduct at the workplace. This study's theoretical and practical significance would guide the stakeholders in corporate management to regulate governance policies based on the right ethical values and promote personalities with high integrity in management conduct. Originality/value: This study promotes a world-class good governance ethics framework in curbing criminal acts for better corporate performance. This new framework is formulated based on the concept of a caliph and other essential elements envisaged by the Quranic verses.